ChemInform Abstract: Asymmetric Hydrogenation of Isoquinolinium Salts Catalyzed by Chiral Iridium Complexes: Direct Synthesis for Optically Active 1, 2, 3, 4‐Tetrahydroisoquinolines. Issue 30 (4th July 2013) - Iimuro, Atsuhiro; Yamaji, Kenta; Kandula, Sathaiah; Nagano, Takuto; Kita, Yusuke; Mashima, Kazushi
Abstract In the presence of a chiral iridium catalyst, 1‐ and 3‐substituted as well as 1, 3‐disubstituted isoquinolinium salts can be hydrogenated, giving the corresponding 1, 2, 3, 4‐tetrahydroisoquinolines in high enantiomeric excess.